Long-term Evolution of Sco X-1: Implications for the Current Spin Frequency and Ellipticity of the Neutron Star - Abhijnan Kar; Pulkit Ojha; Sudip Bhattacharyya (The Astrophysical Journal)
Sco X-1 is the brightest observed extrasolar X-ray source, which is a neutron star (NS) low-mass X-ray binary (LMXB) and is thought to have a strong potential for continuous gravitational waves (CW) detection due to its high accretion rate and relative proximity. Here, we compute the long-term evolution of its parameters, particularly the NS spin frequency ( ν ) and the surface magnetic field ( B ), to probe its nature and its potential for CW detection. We find that Sco X-1 is an unusually young (∼7 × 10 ^6 yr) LMXB and constrain the current NS mass to ∼1.4–1.6 M _⊙ . Our computations reveal a rapid B decay, with the maximum current value of ∼1.8 × 10 ^8 G, which can be useful to constrain the decay models. Note that the maximum current ν value is ∼550 Hz, implying that, unlike what is generally believed, a CW emission is not required to explain the current source properties. However, ν will exceed an observed cutoff frequency of ∼730 Hz, and perhaps even the NS breakup frequency, in the future without a CW emission. The minimum NS mass quadrupole moment ( Q ) to avoid this is ∼(2–3) × 10 ^37 g cm ^2 , corresponding to a CW strain of ∼10 ^−26 . Our estimation of current ν values can improve the CW search sensitivity.